Image Evaluation and Association Analysis of the Cardiovascular Disease of the Degree of Pancreatic Steatosis in Ultrasonography - Cho, Jin-Young; Ye, Soo-Young; Ko, Seong-Jin (Transactions on electrical and electronic materials, 2016)
Increasing fat tissue of obese people, increases the rate of cardiovascular disease, diabetes, metabolic syndromes and dyslipidemia. An increase in the focal tissue of pancreas is a known risk factor of these diseases. Although there exists sufficient research on the diagnosis and treatment of pancreatic cancer, studies have been done on fatty pancreas. In this study, based on ultrasound imaging and using a texture characteristic of GLCM, fatty pancreas was divided into three categories: mild, moderate and severe. We compared and analyzed the three groups was by Pancreatic ultrasonography and body characteristics, serological tests, pressure and the degree of arteriosclerosis, against normal control group. The following parameters of control and test groups were measured: WC (waist circumference),BMI (body mass index), TC (total cholesterol), TG (triglyceride), HDL-C (High-density lipoprotein cholesterol) and LDL-C (Low-density lipoprotein cholesterol), SBP (systolic blood pressure), BST (Blood Sugar Test) and aortic PWV (pulse wave velocity). We observed the values correspondingly increasing fat deposition. However, ABI (Ankle Brachial pressure index) stenosis and HDL-C levels decreased with increasing fat deposit (p <0.05); a drop in these parameters are known to be harmful to the human body. The difference in texture characteristics between normal control group and pancreatic fatty group ( mild, moderate, and severe) was statistically confirmed. Ultrasound imaging of pancreatic steatosis categorized the disease as mild, moderate and severe based on the characteristic texture. In conclusion, we observed on increase in metabolic syndrome, dyslipidemia, and arteriosclerosis, proportional to the degree of pancreatic fat deposition. The escalation of these diseases was confirmed and was directly related with predictors of cardiovascular diseases.